Spatial and temporal distribution of phytoplankton community in relation to environmental factors in the southern coastal waters of Korea - Sun, Yanxu; Youn, Seok-Hyun; Oh, Hyun Joo; Joo, Hui-Tae; Kim, Yejin; Kang, Jae Joong; Lee, Dabin; Kim, Kwanwoo; Jang, Hyo Keun; Jo, Naeun; Yun, Mi Sun; Sun, Linhe; et al. (Frontiers in Marine Science, 2022)
The spatial and temporal environmental conditions in the southern coastal waters of Korea (SCWK) as a complex area, which is influenced by both ocean currents and anthropogenic nutrient inputs, are highly variable. The impacts of environmental factors on the distribution of phytoplankton community structure in the SCWK remain unclear. Based on high-performance liquid chromatography (HPLC) analysis of a variety of photosynthetic pigments, spatial and temporal variations in phytoplankton community compositions were investigated in the SCWK. Cluster analysis, correlation analysis, and generalized additive models (GAMs) were used to explore the major phytoplankton groups and their response patterns to temperature, salinity, depth, and macronutrients. The results indicated that diatoms were the absolute dominant groups in the SCWK for all seasons, especially in cold seasons. Diatoms mainly concentrated at 1% light depths, while high chlorophyll-a concentrations (>3 µg/L) occurred at 100% and 30% light depths with good light conditions. Both clustering and correlation analyses showed that diatoms had a strong positive correlation with macronutrients such as dissolved inorganic nitrogen (DIN), dissolved inorganic phosphate (DIP), and dissolved silica (DSi). The temperature and salinity discrepancy between surface and bottom layers in summer caused a strong water stratification resulting in blocking nutrient-rich bottom water upwelling and leading cyanobacteria to become the dominant groups at 100% and 30% light depths in summer. Consistently, the cyanobacteria were highly associated with high temperature and low salinity in the correlation analysis and GAM results. Compared with diatom-predominant sites, cryptophytes and diatom-dominated sites are characterized by higher average excess nitrate (ExN). Further research on the responses of small-sized prokaryotic phytoplankton especially cyanobacteria to environmental variations and their primary production contributions would warrant a better understanding of the SCWK ecosystem.